Gender and female villains in 21st century fairy tale narratives : from evil queens to wicked witches - Le Clue, Natalie; Vermaak-Griessel, Janelle (Emerald Publishing Limited, 2022)
For every hero, there is a villain, and for every villain there is a story. But how much do we really know about the villain? Filling a gap in the field of gender representation and character evolution, the chapters in this edited collection focus on female villains in the fairy tale narratives of 21st Century media. Within the realm of fairy tale study, the characters of princess, prince, hero, and damsel in distress have been researched extensively, however the female villain has rarely been the central focus of academic study. Gender and Female Villains in 21st Century Fairy Tale Narratives: From Evil Queens to Wicked Witches features chapters from different academic disciplines such as television and film studies, fan studies, character analysis, gender studies, feminist studies and audience analysis. Through the primary lens of gender studies, the collection delves into issues such as vanity, body dysmorphia, femslash fandom, the lesbian gaze, the queering of the villain-hero dichotomy, and morality and femininity. Concluding by looking into physical disability, maternal subversion, and social exclusion, as well as the construct of beauty 'ideals' as applied to female villains, this collection breaks fresh ground by putting the female villain at the centre of academic study.
Keywords: Fairy tales -- History and criticism.; Fairy tales in literature.; Women in literature.; Villains in literature.; Literary Criticism, Fairy Tales, Folk Tales, Legends & Mythology.; "Literary studies: fiction, novelists & prose writers".; elektronické knihy; electronic books